An unconventional outer-to-inner synthesis strategy for core (Au)–shell nanostructures with photo-electrochemical enhancement. Issue 16 (12th April 2017) - Zhang, Zhuo; Baek, Minki; Song, Hongseon; Yong, Kijung
Abstract : In this work, an outer-to-inner strategy is demonstrated to simultaneously fabricate core–shell NPs and assemble them onto a scaffold. Abstract : In this work, an outer-to-inner strategy is demonstrated to simultaneously fabricate core–shell NPs and assemble them onto a scaffold. Specifically, the shell material is deposited onto the scaffold first, and then a layer of the core material (Au) is covered on the shell surface. Finally, the core (Au)–shell nanoparticles (NPs) are formed on the scaffold after annealing. As examples, Au–Bi2 S3, Au–CdS and Au–CdSe core–shell NPs are grown on the surface of ZnO nanorods (NRs) via this strategy and exhibit enhanced photoelectrochemical (PEC) efficiency. The enhanced PEC performance is ascribed to improved light absorption induced by the plasmonic effect, trapped electrons of Au NPs, and cascade band alignment of the shell material and ZnO. The synthetic method gives a universal route to the development of nanodevices with assembled core–shell NPs. The core–shell NPs in the current study possess significant potential as building blocks for future PEC anodes or other solar conversion systems.